Substantive Analytical Procedures in Sharia Compliants as Agreed-Upon Procedures Service in Italian Corporate Governance - Stefano de Nichilo (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
Islamic finance is a complex of banking, financial and insurance activities carried out in accordance with the dictates of Islamic law (shari'a) and which can be framed in the broader genus of ethical or sustainable finance. Since its inception, but especially in the last thirty years, it has experienced constant and surprisingly rapid growth. However, the rise of Islamic finance has remained confined to some specific geographic realities, failing, at least for the moment, to establish solid roots in the European, Australian or American markets. Although Islamic finance began to appear on the European scene as early as the early 2000s, the response of the states was, in general and with some relevant exceptions, rather disappointing. In Italy, for example, the spread of this phenomenon is hindered by the absence of regulatory frameworks, by a distorted narrative and communication as well as by technical and cultural barriers. This work aims to be a reflection on various aspects - historical, social and economic - of Islamic finance of which our country, by virtue of its geopolitical position and its historical traditions, should become more aware.